1998
DOI: 10.1073/pnas.95.13.7316
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of SP100 with HP1 proteins: A link between the promyelocytic leukemia-associated nuclear bodies and the chromatin compartment

Abstract: The PML͞SP100 nuclear bodies (NBs) were first described as discrete subnuclear structures containing the SP100 protein. Subsequently, they were shown to contain the PML protein which is part of the oncogenic PML-RAR␣ hybrid produced by the t(15;17) chromosomal translocation characteristic of acute promyelocytic leukemia. Yet, the physiological role of these nuclear bodies remains unknown. Here, we show that SP100 binds to members of the heterochromatin protein 1 (HP1) families of non-histone chromosomal protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
237
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(250 citation statements)
references
References 48 publications
12
237
0
1
Order By: Relevance
“…In these studies, increasing SP100 concentration in the presence of ETS1 proportionately decreased ETS1 transcriptional activity. SP100 has been shown to interact with heterochromatin protein 1 (HP1), which functions as a transcriptional repressor (Seeler et al, 1998), and SP100 acts as repressor of transcription when tethered to DNA (Lehming et al, 1998;Seeler et al, 1998;Bloch et al, 1999). However, SP100 and ETS1 have recently been reported to coactivate the MMP3 (stromelysin) promoter as well as a heterologous promoter containing multimerized EBS (Wasylyk et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, increasing SP100 concentration in the presence of ETS1 proportionately decreased ETS1 transcriptional activity. SP100 has been shown to interact with heterochromatin protein 1 (HP1), which functions as a transcriptional repressor (Seeler et al, 1998), and SP100 acts as repressor of transcription when tethered to DNA (Lehming et al, 1998;Seeler et al, 1998;Bloch et al, 1999). However, SP100 and ETS1 have recently been reported to coactivate the MMP3 (stromelysin) promoter as well as a heterologous promoter containing multimerized EBS (Wasylyk et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…SP100 was first identified as a nuclear autoantigen in patients with the autoimmune disease Primary Biliary Cirrhosis (Szostecki et al, 1990, and its mRNA and protein is potently induced by interferon (IFN) . SP100 is a constituent member of the nuclear body (NB), a subnuclear organelle, also referred to as Kr-bodies, nuclear domain 10 (ND10) or PML oncogenic domains (PODs) (Lamond and Earnshaw, 1998;Seeler et al, 1998;Seeler and Dejean, 1999). The function of SP100, as well as NBs, remains unknown, although nuclear bodies have been implicated in the development of neoplasia and the progression of viral infection (Lamond and Earnshaw, 1998;Seeler et al, 1998;Seeler and Dejean, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…24 In addition, SP100 can be covalently modified by the ubiquitinlike SUMO-1 protein. Since the SUMO-1 and ubiquitin proteins target the same lysines, it has been suggested that sumoylation of proteins antagonizes their ubiquitination, and thus protects them from ubiquitin-mediated degradation.…”
Section: Discussionmentioning
confidence: 99%
“…First, we determined the subcellular distribution of SP100 that interacts directly with HP1a protein. 24 The G2 cells from ICF patients were immunostained with an anti-SP100 antibody and showed that a high proportion of nuclei have a prominent bright SP100 focus, in addition to a diffuse faint staining of the nucleoplasm. Double immunocytochemistry with differently labelled HP1a and SP100 antibodies clearly demonstrated their perfect nuclear co-localization to the bright focus (Figure 6a).…”
Section: Aberrant Nuclear Distribution Of Hp1a Hp1b and Hp1c Proteinmentioning
confidence: 99%
“…Remarkably, simultaneous expression of PML inhibits the repressive activity of Daxx, possibly by localizing it to the PODs (Lehembre et al, 2001;Li et al, 2000a). Another PODassociated protein, Sp100 (Szostecki et al, 1990), also represses transcription when fused to the Gal4 DBD and contains a heterochromatin1 (HP1) binding domain (Lehming et al, 1998;Seeler et al, 1998). The interaction of Sp100 and HP1 proteins was taken as a mechanistic explanation as to how Sp100 mediates transcriptional repression, i.e.…”
Section: Pml Pods and Transcriptional Regulationmentioning
confidence: 99%